Isosteviol: a potential cardioprotective agent - Jovanović, Aleksandar (Archives of Pharmacy, 2024)
Cardioprotection is a term describing the myocardial property to protect itself from injury, particularly in the context of ischemia-reperfusion injury and other metabolic stresses. Recently, isosteviol, a diterpene derived from the hydrolysis of stevioside, a natural sweetener found in the leaves of the Stevia rebaudiana plant, has emerged as a potential cardioprotective compound. In addition to the many therapeutic benefits of isosteviol, including antihyperglycemic, antihypertensive, and anti-inflammatory effects, recent studies have suggested that this compound might have cardioprotective properties as well. It has been demonstrated that isosteviol possesses antioxidant and anti-inflammatory activities, while also regulating ion channels and mitochondrial activity. The cardioprotective effects of isosteviol are mediated through its interaction with multiple signaling pathways. Pre-clinical work has demonstrated that isosteviol regulates NF-κB, phosphatidylinositol 3-kinase/Akt (PI3K/Akt) pathways, and adenosine monophosphate-activated protein kinase (AMPK), all of which are well-established cardioprotective signaling pathways. All these findings highlight isosteviol’s potential as a cardioprotective therapeutic agent. However, this potential needs to be further tested in randomized controlled trials, along with examining isosteviol’s possible value in clinical practice, defining optimal dosing strategies, and understanding its long-term effects.